THE ADVANTAGES OF USING COMMUNICATION GAMES IN TEACHING ENGLISH AS FOREIGN LANGUAGE - Desi Surayatika (Global Expert: Jurnal Bahasa dan Sastra, 2018)
Games promote learners’ interaction.Interaction comprises the nature of classroom pedagogy and classroom behavior. Pair or group work is one of the main ways to increase cooperation. Many games can be played in pairs or in small groups, thereby providing an opportunity to develop their interpersonal skills such as the skill of disagreeing politely or the skill of asking for help. In the classroom learners will definitely participate in the activities. Therefore, in groups or in pairs, they are more willing to ask questions, communicate and discuss topics with their partners and think creatively about how to use foreign language to achieve their goals. The competition in the games gives students a natural opportunity to work together and communicate with each other a lot.Games improve learners’ language acquisition.Thanks to the motivation and interaction created by games, students can acquire knowledge faster and more effectively than by other means. Games can stimulate and encourage students to participate in the activity since they naturally want to win. Apart from having fun, students are learning. They acquire a new language. Students begin to realize that they have to use the language if they want others to understand what they are saying.Furthermore,games can lower anxiety. In the easy, relaxed atmosphere which is created by using games, students remember things faster and better.The meaning of the language students listen to, read, speak and write in will be more vividly experienced in a game and, therefore, they will better remember the language they learn.Games increase learners’ achievement.Games can involve all the basic language skills, i.e., listening, speaking, reading, and writing, and a number of skills are often involved in the same game.Games can motivate learners, promote learners’ interaction, and improve learners’ acquisition. As a result, games can increase learners’ achievement, which means that learners’ test results, ability of communication, knowledge of vocabulary, or other language skills can improve.Key words: Communication Games, Advantages, English